1993
DOI: 10.1016/0020-7292(93)90155-p
|View full text |Cite
|
Sign up to set email alerts
|

Cervical carcinoma in young patients: Clinical and pathological variables

Abstract: Twenty-five (10.2%) out of 243 untreated patients with invasive cervical carcinoma were 35 years old or younger. When matching the clinical and pathological variables between the younger and the older women, the former were characterized by a higher rate of Stage IB disease (P = 0.10), G3 and G4 tumors (P = 0.25), bulky lesions (P = 0.05) and node metastases (P = 0.50). In spite of this poorer pathological profile, both the 5-year disease-free survival rate (75%) and survival according to stage of the younger … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
2
0
3

Year Published

1996
1996
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 23 publications
1
2
0
3
Order By: Relevance
“…Our study also demonstrated that younger patients were presenting with disease that is more aggressive during the study period; there was a higher frequency of lymph node metastasis and larger tumors, although the tumor size differences were not statistically significant. These findings correspond to findings from other studies and our patients may have a poorer prognosis, as has been similarly noted in previous reports (21)(22)(23).…”
Section: Discussionsupporting
confidence: 94%
“…Our study also demonstrated that younger patients were presenting with disease that is more aggressive during the study period; there was a higher frequency of lymph node metastasis and larger tumors, although the tumor size differences were not statistically significant. These findings correspond to findings from other studies and our patients may have a poorer prognosis, as has been similarly noted in previous reports (21)(22)(23).…”
Section: Discussionsupporting
confidence: 94%
“…Many earlier reports demonstrated a poorer prognosis in young women (2), while some studies indicated no difference or a better prognosis for young patients (3). Therefore, it remains controversial whether young patients with invasive cervical carcinoma have a poorer prognosis than older women.…”
Section: Introductionmentioning
confidence: 93%
“…Se excluyeron aquellos casos no incidentes, aquellos cuyas historias clínicas no estuvieron disponibles, pacientes sin confirmación de diagnóstico patológico y pacientes con lesiones preinvasivas del cuello uterino. Se eligió la edad de 35 años como punto de corte debido a que la incidencia de CC se incrementa notablemente por encima de este límite (10) .…”
Section: Criterios De Selecciónunclassified
“…No obstante, varios estudios epidemiológicos demuestran que la incidencia de CC está aumentando en los grupos etarios más jóvenes (4)(5)(6)(7) . Se han descrito que el cáncer cervical en mujeres jóvenes presenta características más agresivas como presentar enfermedad en estadio avanzado al momento del diagnóstico (8) , tener un mayor tamaño tumoral (8)(9)(10) , presentar una tasa más alta de compromiso parametrial (11) , nodal (10) , y de metástasis a distancia (4) . Asimismo, la mayoría de autores concuerda en que en comparación con pacientes mayores, las jóvenes presentan una mayor incidencia de cáncer de células no escamosas (4,(11)(12)(13) .…”
Section: Introductionunclassified
See 1 more Smart Citation